THE EFFECT OF COMPLETENESS OF FEATURES AND QUALITY OF INFORMATION ON USER SATISFACTION OF THE POSPAY APPLICATION IN KOLAKA REGENCY - Andry Stepahnie Titing; Muhamad Stiadi; Fitri Kumalasari (SEAN Institute, 2023)
The endpoint of this research is to ascertain how Kolaka Regency's Pospay application's feature completeness and information quality affect user satisfaction. According to the study's findings, the Pospay application's user satisfaction in the Kolaka area is unaffected by feature completeness. While the Pospay application's user satisfaction in the Kolaka district is influenced by the information quality variable. With an R Square value of 0.792, or 79.2%, this study's feature completeness and information quality variables have a 79.2% influence on user satisfaction with the Pospay application in Kolaka Regency, while variables not included in the study have a 20.8% influence.